Striving for Human Rights in Drama Rainbow’s End (2005) by Jane Harrison - Zahrayuki Kyoko; An Fauzia Rozani Syafe’i (English Language and Literature, 2023)
This thesis is the analysis of a play which written by Jane Harrison entitled Rainbow’ s End (2005). It explores the issue of striving for human rights by making use of the given opportunities and resisting oppression. It is reflected by the characters in the play. It is also intended to find out the contribution of fictional devices such as character, plot (conflicts) , and setting in revealing the issue of striving for human rights. This analysis is related to the concept of agency in postcolonial theory by Ashcroft et al. that is supported by the text-based and context-based interpretation. The result of this analysis shows about striving for human rights that is experienced by characters by making use of the given opportunities and resisting oppression.